Reliability and validity of badminton special speed training method toward success score and time perception predictive skills performance of badminton players - Nur Ikhwan Mohamad (Tanjung Malim, 2021)
Reliability and validity of badminton special speed training method toward success score and time perception predictive skills performance of badminton players by Nur Ikhwan Mohamad